Impunity as a sanctuary - Camilo Eduardo Umaña Hernández (Oñati Socio-Legal Series)
Impunity as a sanctuary refers to a situation wherein structures are constituted to prevent the legal system from reacting to criminal conduct. Focusing on the state criminality, this study examines the concept of impunity as a form of interference with the legal process. It also analyzes the continuities between the structures of power prompting criminal conduct and the lack of legal sanction. In this sense, the metaphor “sanctuary” shifts the main understanding of impunity as a problem that is exclusive to the internal operation of the criminal system to a wider constraint that supposes studying possible asymmetries of power from the legal system vis-à-vis other powerful actors. With this purpose, this paper considers a number of cases shedding light to structures of denial and obfuscation that allow to understand the particularities of understanding impunity as a sanctuary.